PELANGGARAN PRINSIP KERJA SAMA DAN PEMATUHAN PRINSIP KESANTUNAN DALAM PEMBELAJARAN BAHASA INDONESIA DI SMK PELAYARAN âAKPELNIâ SEMARANG - Fajrin, Rafika; Andayani, Andayani; Rohmadi, Muhammad (Jurnal S2 Pendidikan Bahasa Indonesia, 2016)
This study aimed to describe the type of speech acts used in Indonesian language learning; violation of cooperation principleÂ  in Indonesian language learning; and Compliance politeness principle in Indonesian language learning at SMK Pelayaran "Akpelni" Semarang. This research was conducted at SMK Pelayaran âAkepelniâ Semarang. Object of this research is the teachers and students in the Indonesian language learning at classroom. Data were collected through observation and techniques used SLBC. Samples were taken by using purposive sampling technique. Data was validated using triangulation techniques and source triangulation theory. Data were analyzed using data analysis interactive model. The results showed that, 1) the teacher and student use of speech acts, such as locution, illocution, and perlocution; 2) violation of cooperation principle undertaken by teachers and students is the maxim of quantity, maxim of quality, maxim of relevance, and the maxim of manner; and 3) adherence to the principles of politeness done by teachers and students is the tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim.